EDUKASI SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) KEPADA PEGAWAI PENDAFTARAN TENTANG MUTU PENDAFTARAN RAWAT JALAN DI RSU HAJI MEDAN - Apriana, Ana; Bukit, Herawati; Manullang, Hengki Frengki; Tarigan, Usaha; Sitepu, Pani Febriyanti (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
This community service aims to increase understanding of Health Information Management Information Systems (SIMRS) and its role. Measuring quality covers many dimensions and reliability is key - ensuring fast, accurate and satisfactory service. Achieving these functions requires the implementation of a web-based information system known as a hospital information management system. The methodology used includes a focus group discussion (FGD), which reveals that the implementation of SIMRS, especially in the implementation of RME, improves the quality of health services and operational efficiency in outpatient registration. The most important benefits identified are enhanced collaboration between departments. A final evaluation will be done to evaluate the participants and #039; understanding the importance of electronic patient records in improving work processes. Evaluation includes questions to all participants and drawing conclusions from the results of the analysis and evaluation. In conclusion, the community service confirms that the use of electronic patient records in Haji Medan Hospital facilitates the tasks of the staff.